Antimicrobial-Resistant Klebsiella pneumoniae Carriage and Infection in Specialized Geriatric Care Wards Linked to Acquisition in the Referring Hospital. (11th January 2018) - Gorrie, Claire L; Mirceta, Mirjana; Wick, Ryan R; Judd, Louise M; Wyres, Kelly L; Thomson, Nicholas R; Strugnell, Richard A; Pratt, Nigel F; Garlick, Jill S; Watson, Kerrie M; Hunter, Peter C; McGloughlin, Steve A; et al.
Abstract : Patients' own gut microbiota were the major source of Klebsiella pneumoniae, but extended-spectrum β-lactamase strains were acquired in the referring hospital. This highlights the potential for rectal screening, and the importance of the wider hospital network, for local risk management. Abstract: Background: Klebsiella pneumoniae is a leading cause of extended-spectrum β-lactamase (ESBL)–producing hospital-associated infections, for which elderly patients are at increased risk. Methods: We conducted a 1-year prospective cohort study, in which a third of patients admitted to 2 geriatric wards in a specialized hospital were recruited and screened for carriage of K. pneumoniae by microbiological culture. Clinical isolates were monitored via the hospital laboratory. Colonizing and clinical isolates were subjected to whole-genome sequencing and antimicrobial susceptibility testing. Results: K. pneumoniae throat carriage prevalence was 4.1%, rectal carriage 10.8%, and ESBL carriage 1.7%, and the incidence of K. pneumoniae infection was 1.2%. The isolates were diverse, and most patients were colonized or infected with a unique phylogenetic lineage, with no evidence of transmission in the wards. ESBL strains carried bla CTX-M-15 and belonged to clones associated with hospital-acquired ESBL infections in other countries (sequence type [ST] 29, ST323, and ST340). One also carried the carbapenemase bla IMP-26 . Genomic and epidemiological data provided evidence that ESBL strains were acquired in the referring hospital. Nanopore sequencing also identified strain-to-strain transmission of a bla CTX-M-15 FIBK /FIIK plasmid in the referring hospital. Conclusions: The data suggest the major source of K. pneumoniae was the patient's own gut microbiome, but ESBL strains were acquired in the referring hospital. This highlights the importance of the wider hospital network to understanding K. pneumoniae risk and infection prevention. Rectal screening for ESBL organisms on admission to geriatric wards could help inform patient management and infection control in such facilities.